DEFENSE OF SUNDANESE IN CHILDREN USING A BILINGUAL PICTURE STORYBOOK: A PSYCHOLINGUISTIC APPROACH - Triyanto Triyanto; Nina Nina (STKIP Siliwangi, 2023)
Language as an embodiment of the human mind has a relationship with the field of psychology. The phenomenon of families who speak Sundanese but prefer to teach Indonesian and foreign languages to their children is what inspired this research. If left unchecked, there will be a shift and the potential to cause the extinction of the Sundanese language. This study aims to describe the phenomenon of Sundanese-speaking families who choose to teach Indonesian and other languages to their children, resulting in widespread adoption of Indonesian and foreign languages in the family. This research method is qualitative with interview and observation approach. There are five children from five different schools. Each child was treated by giving readings in the form of bilingual picture story books. Researchers also interviewed each child. The test was carried out for three times, namely pre-test, cycle 1, and cycle 2. The test results showed that giving readings with bilingual picture story books could increase the mastery of Sundanese vocabulary in the five children as respondents. According to the findings of this study, treatment with bilingual picture story books can preserve Sundanese in children and lead to an increase in Sundanese speakers from an early age.